A comparison of angle measure reproducibility between manual and computerized tracing - Bonilla-Londoño, Margarita María; Barrera-Chaparro, Judith Patricia; Arroyave-Godoy, Ángela Patricia; Díaz-Roa, Mónica Eliana (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: digital cephalometry allows handling errors produced during manual tracing; the purpose of this study was therefore to evaluate the reproducibility and precision of angle measures between manual tracing and that obtained with Cephapoint in digital radiography. Methods: 11 direct digital radiographs taken to orthodontics students were introduced in the Cephapoint computer program. 9 angles were measured in both hand-tracing digital radiography and Cephapoint. All measurements were made by 3 operators with 1-week interval. We calculated the average interobserver error to find the reproducibility of each angle measure, and the average intra-observer error to determine the accuracy of each observer. Results: the FH/N/Pg angle showed the smallest interobserver error difference (0.10°) in both methods, favoring manual tracing. On the other hand, the angles with the smallest inter-observer error difference in computerized tracing were LI-NB (0.11°) and N-A/Pg (0.11°). Intraobserver reproducibility showed excellent Intraclass Correlation Coefficient (ICC) in both methods. Conclusions: reproducibility of angular measurements did not show significant differences between manual and computerized tracing. According to the findings of this study, the methods under evaluation offer equal diagnostic validity.